FORMING FINE WRITING SKILLS IN ELEMENTARY GRADES - Narziyeva Sarvinoz (Scholar Express Journals, 2021)
This article provides information on how to form beautiful writing skills in elementary school students.
Keywords: Hygienic rules, calligraphy, workplace, writing instruments, pen, whose of letter is beautiful